Hungary : Financial System Stability Assessment Update, including a Report on the Observance of Standards and Codes on Insurance Regulation. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents an update to Hungary's Financial System Stability Assessment, including a Report on the Observance of Standards and Codes on Insurance Regulation. The assessment reveals that financial intermediation in Hungary has continued to deepen. The expansion of bank lending at higher interest margins has resulted in a sharp increase in bank profitability. Although financial soundness indicators show that the banking system has evolved well overall, potential risks have emerged, which should be carefully monitored and appropriately addressed. Nonbank financial institutions remain relatively small and are not currently a source of systemic vulnerability.